Optimized radiofrequency lesions through local impedance guidance for effective CTI ablation in right atrial flutter. Issue 5 (22nd April 2022) - Ducceschi, Valentino; Zingarini, Gianluca; Nigro, Gerardo; Brasca, Francesco Maria Angelo; Malacrida, Maurizio; Carbone, Angelo; Lavalle, Carlo; Maglia, Giampiero; Infusino, Tommaso; Aloia, Antonio; Nicolis, Daniele; Auricchio, Claudia; et al.
Abstract: Background: Although radiofrequency (RF) catheter ablation of cavo‐tricuspid isthmus (CTI) is an established treatment for typical right atrial flutter (RAFL), it remains to be established whether local tissue impedance (LI) is able to predict effective CTI ablation and what LI drop values during ablation should be used to judge a lesion as effective. We aimed to investigate the ability of LI to predict ablation efficacy in patients with RAFL. Methods: RF delivery was guided by the DirectSense™ algorithm. Successful single RF application was defined according to a defragmentation of atrial potentials (DAP), reduction of voltage (RedV) by at least 80% or changes on unipolar electrogram (UPC). The ablation endpoint was the creation of bidirectional conduction block (BDB) across the isthmus. Results: 392 point‐by‐point RF applications were analyzed in 48 consecutive RAFL patients. The mean baseline LI was 105.4 ± 12Ω prior to ablation and 92.0 ± 11Ω after ablation ( p < 0.0001). According to validation criteria, absolute drops in impedance were larger at successful ablation sites than at ineffective ablation sites (DAP: 17.8 ± 6Ω vs. 8.7 ± 4Ω; RedV: 17.2 ± 6Ω vs. 7.8 ± 5Ω; UPC: 19.6 ± 6Ω vs. 10.1 ± 5Ω, all p < 0.0001). LI drop values significantly increased according to the number of criteria satisfied (ranging from 7.5Ω to 19.9). BDB was obtained in all cases. No procedure‐related adverse events were reported. Conclusions: A LI‐guided approach to CTI ablation was safe and effective in treating RAFL. The magnitude of LI drop was associated with effective lesion formation and BDB and could be used as a marker of ablation efficacy. Clinical trial registration: Catheter Ablation of Arrhythmias with a High‐Density Mapping System in Real‐World Practice (CHARISMA). URL: http://clinicaltrials.gov/ Identifier: NCT03793998.